Sage, humanist, and physician to all men: Keats and Romantic Conceptualisations of the Poet. Issue 2 (July 2016) - O'Halloran, Meiko
Abstract : In the aftermath of the French Revolution which failed to give birth to a hoped-for new egalitarian age in Britain, radically-minded poets were forced to confront the question of what their role was in a post-Revolutionary age. This article examines Keats's distinctive contribution to the debates of his day by exploring his crafting of the figure of the poet in Hyperion and The Fall of Hyperion . What do Keats's sympathetic portraits of the fallen Titans and the unrealised perfection of Apollo have to tell us about his conceptions of the poet? I begin by looking back to influential models of the epic poet by Dante, Milton, and Macpherson which Keats and his contemporaries inherited, before examining the extraordinary debate with Moneta in The Fall of Hyperion in which the poet-narrator defends the poet as 'a sage, / A humanist, physician to all men', only to destabilise his own claim to the title.